THE EFFECT OF FIELD WORK PRACTICE ON VOCATIONAL STUDENTS' WORK READINESS AND CAREER MOTIVATION - Abadiyah, Lisalamah; Yayuk, Erna; Restian, Arina (Universitas Labuhanbatu, 2025)
Purpose: This study aims to determine the effect of Field Work Practice (PKL) on work readiness and career motivation of vocational high school students. The high unemployment rate among vocational high school graduates indicates a gap between graduate competencies and the demands of the world of work. Therefore, increasing work readiness and career motivation is crucial in bridging the gap and preparing students to face the world of work optimally.Methodology: This study uses a quantitative approach with a causal design. The sample consisted of 78 grade XII students of the Motorcycle Engineering Department at SMK PGRI 5 Jember who were selected through purposive sampling techniques. Data were collected using a validated Likert scale questionnaire, covering indicators of field work practice implementation, work readiness, and career motivation. Data analysis was performed using simple linear regression.Findings: The results of the study showed that field work practice had a positive and significant influence on work readiness (p < 0.001; t = 8.366) and students' career motivation (p = 0.002; t = 3.772). These findings indicate that direct involvement in the world of work during field work practice contributes to increasing technical competence, mental readiness to face the challenges of the world of work, and strengthening students' orientation and enthusiasm in planning their future careers.Contribution: This study shows that fieldwork practice is an effective strategy to simultaneously improve work readiness and career motivation of vocational high school students. Therefore, it is necessary to strengthen the implementation structure of fieldwork practice and closer collaboration between schools and the industrial world. These findings can be the basis for developing more relevant and adaptive vocational curriculum and vocational education policies. In addition to providing technical skills, fieldwork practice also plays a role in developing 21st century competencies.